ROM - Review Opinion Mining a Novelized Framework - Vivekanandan, K; Helen Josephine, VL (International Journal of Computer Sciences and Engineering, 2014)
Today, as a result of the global internet viewers increased rapidly, consumers are more focused than ever on searching the best product and the best prices. Consequently, e-commerce corporations also invested their time, money and efforts to know the feedback and comments about their products. That would help the corporations to modernize their product at low prices, which in turn help them to extend and prosper in their business. Customer / Product review is an evaluation of the product performance and comment on the reliability and whether or not the product delivers on these promises. Now-a-days, online reviews are the recent media world-of-mouth, they are enormously influential and may have an enormous effect on however business is perceived. Since, overwhelming information on one product is available in the form of review, individuals or corporation finds very difficult to analyse each and every review to extract knowledge from that pool of unstructured data. So, to analyse and to extract knowledge from these large amounts of data automatic method must be developed. This paper describes the ROM framework for developing such an automatic method to mine the opinion from the online product reviews.